The role of B7-H4 in ovarian cancer immunotherapy: current status, challenges, and perspectives - Zhou, Lu; Duan, Yuanqiong; Fu, Kaiyu; Zhang, Mengpei; Li, Kemin; Yin, Rutie (Frontiers in Immunology, 2024)
Immunotherapy stands as a critical and auspicious therapeutic approach in the fight against cancer nowadays. Immune checkpoint inhibitors, in particular, have garnered widespread employment and delivered groundbreaking therapeutic outcomes across various malignancies. However, the efficacy is unsatisfactory in the ovarian cancer. The pressing concerns of the substantial non-response rate require immediate attention. The pursuit of novel targets and the formulation of synergistic combination therapy approaches are imperative for addressing this challenge. B7-H4, a member of the B7 family of co-inhibitory molecules, exhibits high expression levels in ovarian cancer, correlating closely with tumor progression, drug resistance, and unfavorable prognosis. B7-H4 has the potential to serve as a valuable biomarker for evaluating the immune response of patients. Recent investigations and preclinical trials focusing on B7-H4 in the context of ovarian cancer immunotherapy highlight its emergence as a promising immunotherapeutic target. This review aims to discuss these findings and anticipate the future prospects of leveraging B7-H4 in ovarian cancer immunotherapy and targeted therapy.